Entre os documentos oficiais e a prática pedagógica : o uso das TIC no ensino de língua portuguesa no Colégio Estadual Atheneu Sergipense - Santos, Maria Conceição Lima (2016)
This research aims to verify how ICT have been used in the teaching of the Portuguese Language at "Colégio Estadual Atheneu Sergipense" (CEAS), located in Aracaju, Sergipe. Therefore, this research starting with the analysis of official documents nationwide: Lei de Diretrizes e Bases (LDB), 1996; Plano Nacional de Educação (PNE), 2014; Parâmetros Curriculares Nacionais para o Ensino Médio (PCNEM), 1996; Diretrizes Curriculares para o Ensino Médio (DCNEM), 1998 and the Plano de Desenvolvimento da Educação (PDE), 2007; and in local level, the Pedagogical Political Project of the CEAS with the intention of examining how such documents address the ICT employment in education, performing a critical/analytical reading with the help of qualitative/ quantitative words frequency analysis software NVivo. The research is also based on investigations did by Andrade (2013), Geraldi and Geraldi (2012), Xavier and Marcuschi (2010), Barros (2008) and Cereja (2002), and interviews with the Director, the Pedagogical Coordination and Portuguese Language teachers of the CEAS. From these three axes, official documents, literature review and interviews, which are in the research methodology, looking respond to guiding the research questions: What do the official documents about the Portuguese Language teaching in Education average on the use of technology in the classroom by the teacher? As these documents guide the educational practice of the teacher in the classroom and the use of texts and digital tools? What have been the ICT resources currently used by teachers of Portuguese in high school classroom? As ICT has been, in fact, used in pedagogical practice of Portuguese? The object of study, the CEAS is an institution recognized in the state for their excellence and innovative spirit, obtaining the best results in ENEM between state schools in Sergipe. From the results achieved with the collection of data was verified that the use of ICT in LP education in CEAS still happens in a timely and fragmented way, although the school has available infrastructure and qualified teachers, pointing to difficulties with respect to stiffness the curriculum and the priority for the results of ENEM.